2019
DOI: 10.1111/joa.13117
|View full text |Cite
|
Sign up to set email alerts
|

A transmural gradient of myocardial remodeling in early‐stage heart failure with preserved ejection fraction in the pig

Abstract: Heart failure with preserved ejection fraction (HFpEF) is characterized by diastolic dysfunction. This study aimed to analyze whether early HFpEF is already associated with ultrastructural alterations and whether they differ quantitatively among the layers of the left ventricular wall. HFpEF was induced in pigs by deoxy‐corticosterone acetate (DOCA) treatment along with a high‐salt/high lipid diet over 3 months and compared with weight‐matched normal pigs (n = 5 each). Samples of the left ventricle were taken … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 30 publications
0
8
0
2
Order By: Relevance
“…With a more limited coronary microembolization than in the creation of heart failure with reduced ejection fraction, dogs developed heart failure with preserved ejection fraction [ 81 ]. In pigs with corticosterone-induced hypertension, heart failure with preserved ejection fraction developed and was characterized by decreased coronary reserve, [ 192 ] but no alteration in capillary density [ 152 ]. Pigs with chronic aortic banding developed LV hypertrophy with both systolic and diastolic dysfunction but still had preserved ejection fraction; [ 51 ] in this model, the increment in coronary blood flow for a given increase in myocardial oxygen consumption during pressure load was attenuated, suggesting impaired metabolic coronary vasodilation [ 51 ].…”
Section: Heart Failure Of Ischemic and Non-ischemic Originmentioning
confidence: 99%
“…With a more limited coronary microembolization than in the creation of heart failure with reduced ejection fraction, dogs developed heart failure with preserved ejection fraction [ 81 ]. In pigs with corticosterone-induced hypertension, heart failure with preserved ejection fraction developed and was characterized by decreased coronary reserve, [ 192 ] but no alteration in capillary density [ 152 ]. Pigs with chronic aortic banding developed LV hypertrophy with both systolic and diastolic dysfunction but still had preserved ejection fraction; [ 51 ] in this model, the increment in coronary blood flow for a given increase in myocardial oxygen consumption during pressure load was attenuated, suggesting impaired metabolic coronary vasodilation [ 51 ].…”
Section: Heart Failure Of Ischemic and Non-ischemic Originmentioning
confidence: 99%
“…If accounting for lateral contributions of 20%, as previously reported [ 7 ], the global proportion of CX43 should be close to 2% of the cell area. Some studies have suggested that CM represents 80% of volume fraction [ 31 ], but that proportion would be lower for 2D longitudinal sections as compared to 3D volumes. Thus, 2% of CX43 per CM area would be translated into CX43-to-tissue fraction of 1.6% or less.…”
Section: Discussionmentioning
confidence: 99%
“…There are marked differences in cellular composition during development, between males and females (Squiers et al 2020), between atria and ventricles of the same individual (Litviňuková et al 2020) and between healthy and diseased tissue. Myocardial volume is generally dominated by CM (>60% of tissue volume, Mühlfeld et al 2020). The remaining tissue volume comprises non-CM (such as FB, pericytes, neurons, endothelial cells, immune cells, adipocytes or smooth muscle cells), vascular (arterial, capillary, venous and lymphatic) lumens and ECM (the latter with a volume fraction of ≈2-7%, Díez et al 2002;Borbély et al 2005).…”
Section: Composition Of Cardiac Tissuementioning
confidence: 99%